1985
DOI: 10.1017/s0001867800014695
|View full text |Cite
|
Sign up to set email alerts
|

Thinning of point processes—covariance analyses

Abstract: Cross-covariances between the Bernoulli thinned processes of an arbitrary point process are determined. When the point process is renewal it is shown that zero correlation implies independence. An example is given to show that zero covariance between intervals does not imply zero covariance between counts. Mark-dependent thinning of Markov renewal processes is discussed and the results are applied to the overflow queue. Here we give an example of two uncorrelated but dependent renewal processes, neither of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…[15]) and using formulas similar to (10) that appear in that reference. For the simple case of the M/M/1/1 queue, an explicit expression was obtained for the limiting correlation coefficient between the outputs and the overflows in [6]. We now extend this result:…”
Section: Asymptotic Correlation Between Outputs and Overflowssupporting
confidence: 65%
See 2 more Smart Citations
“…[15]) and using formulas similar to (10) that appear in that reference. For the simple case of the M/M/1/1 queue, an explicit expression was obtained for the limiting correlation coefficient between the outputs and the overflows in [6]. We now extend this result:…”
Section: Asymptotic Correlation Between Outputs and Overflowssupporting
confidence: 65%
“…[6]). This is a 2 state CTMC and it is the only M/M/1/K queue that has a renewal output process (cf.…”
Section: Asymptotic Variance Rate Of Birth-death Queuesmentioning
confidence: 99%
See 1 more Smart Citation
“…But since R (t, 0) =°for all t then, asymptotically, we have a stationary renewal process being thinned to produce two uncorrelated processes. But by Chandramohan et al (1985) this implies F is exponential with parameter A and hence H(t) = At. The technical details are to be found in Theorem 3.1 of Chandramohan et al Thus it only remains to show that G(t) = 1 -exp( -At).…”
Section: Arbitrarily Delayed Renewal Processesmentioning
confidence: 99%
“…In a recent paper, Chandramohan et al (1985) studied the cross-correlation structure between the two processes obtained by thinning a point process under various assumptions. Specifically, it was shown that when a stationary or ordinary renewal process is thinned by an independent Bernoulli process, the resulting processes will be uncorrelated if and only if the original process is Poisson.…”
Section: Doubly Stochastic Poisson Processesmentioning
confidence: 99%